Can All Benign Gallbladder Diseases be Managed Laparoscopically? - Ratan, Md Ezharul Haque; Alam, Hasina; Karim, Md Abdul (BIRDEM Medical Journal, 2017)
Background: Laparoscopic cholecystectomy (LC) operation is widely practiced in gallbladder diseases. However, controversy persists for LC in acute gall bladder disease, as risk of complications appears to be greater than open procedure1. This study presents the outcome of LCs performed as the first option of treatment in benign chronic as well as acute gall bladder diseases. Methods: Twelve hundred consecutive patients of gall bladder disease, both acute and chronic, underwent cholecystectomies by a single surgeon using standard four port technique. Age, sex, diabetes, prior abdominal procedures, per-operative findings, additional procedure done and complications directly related to surgical technique were evaluated. Results: The laparoscopic approach was attempted in all patients of this series. Success rate was 99.58%. Non diabetic patients presented much earlier for surgery then diabetic patients. About one third (31.4%) of the patients had acute cholecystitis and its complications and none of them required conversion. Conversion rate was seen among those with long history of gall stone and fibrosed contracted gall bladder at ultrasonography. There were three bile duct injury cases among which two were managed laparoscopically and one needed conversion. Most of the patients (94.5%) were discharged within 20 hours of surgery. There was one mortality (0.08%) in this series. Conclusion: LC has proved to be an effective and safe day case surgical procedure for benign gall bladder pathologies and their complications. It provides much benefits with low complication and conversion in experienced hands. Birdem Med J 2018; 8(1): 35-41